Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12967-017-1133-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation of donor-specific Tr1 cells to be used after kidney transplantation and definition of the timing of their in vivo infusion in the presence of immunosuppression

Abstract: BackgroundOperational tolerance is an alternative to lifelong immunosuppression after transplantation. One strategy to achieve tolerance is by T regulatory cells. Safety and feasibility of a T regulatory type 1 (Tr1)-cell—based therapy to prevent graft versus host disease in patients with hematological malignancies has been already proven. We are now planning to perform a Tr1-cell—based therapy after kidney transplantation.MethodsUpon tailoring the lab-grade protocol to patients on dialysis, aims of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…generated in vitro can be purified from bulk cultures using CD49b and LAG-3 antibodies (Amodio et al, 2015;Gagliani et al, 2013b;Mfarrej et al, 2017;Petrelli et al, 2015). The frequency of CD4 + CD45RA -CD49b + LAG-3 + cells correlates with the expression of IL-10 in human (Amodio et al, 2015;Mfarrej et al, 2017;Petrelli et al, 2015;Sutavani et al, 2013;Tousa et al, 2017;Yao et al, 2015;Tousa et al, 2017), and with induction of immunological tolerance in different preclinical and clinical settings Gagliani et al, 2013b;Kim et al, 2018;Koch et al, 2015;Zhu et al, 2018). Using single-cell mass cytometry, we have shown that CD49b and LAG-3 were sufficient to identify a population of CD4 + CD45RAcells, which is distinct from Th1, Th2, Th17, Tfh, and Treg cells.…”
Section: Phenotype Of Murine and Human Tr1 Cellsmentioning
confidence: 99%
“…generated in vitro can be purified from bulk cultures using CD49b and LAG-3 antibodies (Amodio et al, 2015;Gagliani et al, 2013b;Mfarrej et al, 2017;Petrelli et al, 2015). The frequency of CD4 + CD45RA -CD49b + LAG-3 + cells correlates with the expression of IL-10 in human (Amodio et al, 2015;Mfarrej et al, 2017;Petrelli et al, 2015;Sutavani et al, 2013;Tousa et al, 2017;Yao et al, 2015;Tousa et al, 2017), and with induction of immunological tolerance in different preclinical and clinical settings Gagliani et al, 2013b;Kim et al, 2018;Koch et al, 2015;Zhu et al, 2018). Using single-cell mass cytometry, we have shown that CD49b and LAG-3 were sufficient to identify a population of CD4 + CD45RAcells, which is distinct from Th1, Th2, Th17, Tfh, and Treg cells.…”
Section: Phenotype Of Murine and Human Tr1 Cellsmentioning
confidence: 99%
“…In addition, other suppressive cells not belonging to the Th lineage include CD3 + CD4 − CD8 − double‐negative T cells, Qa‐1‐restricted CD8 Tregs and CD28 lo CD8 + Tregs . While these additional regulatory T‐cell subsets have not been as well studied as the conventional CD4 + Foxp3 + Tregs that are discussed in this review, there is evidence for their protective involvement in renal disease …”
Section: Subsets Of Suppressive T Cellsmentioning
confidence: 97%
“…These protocols have been generating cells that maintain their phenotype including demethylation of the FOXP3 TSDR . Furthermore, Tr1 cells can also be generated from patients with end‐stage kidney disease who are on dialysis …”
Section: Regulatory T Cells In Renal Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…94 DC10-expanded Tr1 cells have also been selected to be a part of the ONE Study to assess the safety, clinical practicality and therapeutic efficacy in kidney transplanted recipients. 95,96 Despite the limited use of Tr1 in present clinical studies, with increased recognition of their importance in controlling T1D and other autoimmune and inflammatory diseases, 41,43,97 a broader use of Tr1 cells might be forthcoming.…”
Section: Modification Of DC Function To Promote T Regmentioning
confidence: 99%